CORAL REEF ECOSYSTEM MANAGEMENT IN AREA OF EASTERN COASTAL WATER CONSERVATION WEH ISLAND SABANG - Nurul Najmi; Mennofatria Boer; Fredinan Yulianda (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2016)
Coral reef ecosystem is important for coastal resources.Damage of Coral reefs resulted in de-gradation of population and fishes reef diversity. The East coast ofWeh Island in Sabang designated as conversation area that has aim to keep coral reefs from destructive utilization activites.The purpose of this study was to know the status of coral reefecosystemsmanagement in marine protected areaEast CoastWeh Island, Sabang and to analyze theattributessensitivelyfromthedimension ofecological,socio-economicand institutional sector.The methodthat used toknow the statusof the sustainablemanagementis RAPFISHanalysis.Dimensions oftheecologycan be known by measuring the coral growth used thePointInterceptTransect,reef fishabundanceusedUnderwaterVisualCensusFishmethod.Socio-economicand institutionaldimensionswill be collected through Focus Group Discussion(FGD) and help by questionnaires.Management status of coral reef ecosystems in the region of the East coast Weh islandmultidimensionallyindicatesthat it was quitesustainable.The most sensitiveattributeofthe managementisthe growth ofsaplings ofcorals,reef fishabundance,conflicts betweenfishermen,the public perceptionagainstthe abundance of fish, the role of the community, and the fishingmanagements.